Politik Hukum dalam Reformasi Regulasi di Indonesia: (Antara Kepentingan Politik dan Kepentingan Elit) - Budiman Basarah; Ulfia Hasanah (Riau Law Journal, 2024)
Regulatory reform in Indonesia has become an important effort to simplify overlapping regulations and support economic growth. However, this policy is often questioned as to whether it prioritizes the interests of political and economic elites over the interests of the broader public. This article aims to analyze the role of legal politics in regulatory reform, focusing on how decision-making in policy formation is influenced by certain interests. The method used in this paper is a literature review and qualitative analysis of the existing legal political dynamics. The main findings indicate that legal politics often creates an imbalance between the interests of elites and the public, potentially undermining social justice in the regulatory process. Regulatory reforms aimed at accelerating economic development may, in fact, worsen social inequalities and strengthen the dominance of certain groups. The impact of this imbalance is the potential decline in social legitimacy of the policies enacted, as well as the emergence of distrust in the existing legal system. Therefore, it is crucial to consider aspects of social justice and transparency in every step of legal reform taken by the government to ensure that the policies generated can create inclusive and sustainable development.